The current status of primipara's childbirth experience and its correlation with their reproductive intention: a cross-sectional survey study - Shan Huang; Mingyang Zhang; Xiaoping Luo; Wenting Yang; Shiying Wang; Jing Zhang; Jinguo Zhai (BMC, 2024)
Abstract Background The childbirth experience of primipara profoundly impacts her future physical and mental health, reproductive intention, and choice of childbirth mode. This study aimed to explore the current situation of primipara's childbirth experience, to analyze the factors influencing negative childbirth experience, and to explore the relationship between childbirth experience and reproductive intention. Methods A cross-sectional survey of a convenience sample of 522 primipara 1-5 days postpartum was conducted at five hospitals in Guangdong Province (May to July 2024). Data were collected using the General Information Questionnaire, the Social Support Rating Scale, the Childbirth Readiness Scale, the Caring Behaviors Inventory Scale, the Wijma Delivery Experience Questionnaire, and the Questionnaire on Reproduction Intention of Primipara. Results The mean score of fear of childbirth was 68.86 ± 17.68. A total of 137 respondents met the clinical criteria for fear of childbirth (≥ 85 points), indicating that 26.2% of primipara had a negative experience of childbirth. Binary logistic regression model showed that elderly primipara [odds ratio (OR) (95% confidence interval (CI)): 11.167 (2.737-45.559)], pregnancy comorbidities or maternal childbirth complications [OR (95%CI): 6.596 (3.046-14.287)], childbirth intervention [OR (95%CI): 6.168 (2.869-13.258)], and severe pain [OR (95%CI): 4.660 (2.197-9.882)] were risk factors for negative childbirth experience. Childbirth accompaniment [OR (95%CI): 0.081 (0.018-0.368)], high level of social support [OR (95%CI): 0.768 (0.704-0.839)], and high level of childbirth readiness [OR (95%CI): 0.878 (0.812-0.950)] protected against a negative birth experience. There was a negative correlation between the fear of childbirth score and reproduction intention scores. Conclusions Childbirth accompaniment and high levels of social support and childbirth readiness can reduce primipara's perception of negative childbirth experience. Negative childbirth experience can reduce reproduction intention.